COX-2 Gene Promoter Methylation in Patients Infected with Helicobacter Pylori. (January 2013) - Michikawa, Yosuke; Yasuda, Hiroshi; Watanabe, Yoshiyuki; Oikawa, Ritsuko; Ohishi, Yoshichika; Maehata, Tadateru; Itoh, Fumio
Cyclooxygenase (COX) plays a critical role in peptic ulcer development. COX-2 contains CpG islands in promoter area, which suggests possible epigenetic mechanisms of gene silencing. We evaluated COX-2 gene promoter methylation levels in the gastric mucosa of patients with various gastric diseases. DNA was extracted from endoscopic biopsy materials collected from the gastric mucosa. The methylation levels of the COX-2 gene promoter were measured quantitatively by using pyrosequencing. COX-2 mRNA expression in Kato III and AGS cells was measured using real-time PCR. COX-2 gene promoter methylation levels were significantly higher in Helicobacter pylori (HP)-positive cases than in HP-negative cases (27.5% vs. 8.1%, respectively, P < 0.001). COX-2 gene promoter methylation levels in patients in whom HP was successfully eradicated were significantly lower than those in HP-positive cases (18.7% vs. 27.5%, respectively, P < 0.01). We then investigated the effects of COX-2 gene promoter methylation on its mRNA expression in vitro. COX-2 mRNA expression was not observed in Kato III cells, despite the addition of the protein kinase C stimulator a-phorbol 12, 13-dibutyrate (PDBu). COX-2 expression was observed after the addition of the demethylating agent 5-Aza-dC and was enhanced by PDBu. HP infection caused a significant increase in the methylation levels of the COX-2 gene promoter in the gastric mucosa. In addition to transcriptional regulation, COX-2 expression is regulated through epigenetic mechanisms.